Family Tracker - Mandadi Venkata, Uma Maheshwar Reddy (Kansas State University, 2017)
People always want know the whereabouts of their loved ones. They want to make sure everything is fine and that they are safe all the time. In this modern age, almost everyone owns a smart phone, which they tend to keep on them all the time. By using these smartphones, we can locate a person anywhere in this world. Android is open source software stack and has the highest smart phone user base. Hence, this application is developed in android. The Family Tracker is an android Application used for finding whereabouts of a person in the most efficient and simple manner. Here we will be having guardians and subjects (users), where users add other people as their guardians. When the user does not lift the phone, the details of his location are sent to the guardian in the form of an SMS. Here the address along with the location link will be sent, using which we can locate it in the map. Guardian can also get the location of user by sending out an SMS to his phone. A one click messaging service is also implemented in this application through which guardian can send message to user’s friends in one click for further inquiry. In order to make this application more helpful for the users, Geo-Fencing is implemented through which guardian can know whether the subject is in or around a particular place (location) of interest (Ex: a university).
Keywords: Android; Geofencing; Location Services